Epidemiology and management burn problems in Marrakech: Report of 15 years of studies what solutions are we considering? - O. Aitbenlaassel; I. Zine-Eddine; O. Elatiqi; Z. Alami; L. Idelkhir; Y. Lamalla; I. Yafi; M. Mahrouch; M.El Gouatri; D. Elamrani; Y. Benchamkha (Elsevier, 2022)
This is a retrospective study spread over 15 years has shed light on the economic and health infrastructure problems in a particularly poor and illiterate population, thus proposing solutions that can improve patient care, reduce complications and allow good social integration, academic and professional.